Virtual Tourism: An Imaginary Art Museum of Soekarno’s Painting Collection Series - Yuke Ardhiati; Ashri Prawesthi D; L. Edhi Prasetya; Febri Wahyu Kurniawan; Bagus Priyambodo (Catuspata Press, 2021)
Abstract : Purpose: This study is concerned with the challenge of how to creatively appreciate Soekarno the first president of Indonesia’s series of painting collections. Research methods: Based on multidisciplinary approaches it was composed of an imaginary building as well as Soekarno’s virtual art museum gallery. Findings: During his life, Soekarno (1901-1970) was fond of collecting numerous of masterpiece paintings and sculptures all of which beautified in six Presidential Palaces. By accommodating interest points in museum buildings and applying Jenck’s theory of postmodern architecture, a virtual or imaginary museum was created. A video depicting the artwork was uploaded on YouTube channel, which serves as Soekarno’s legacy. Implications: Because it is presented in cyber space, it can be easily accessed, and to be a virtual tourism.